PENGARUH LOKASI USAHA DAN MODAL USAHA TERHADAP PENDAPATAN PEDAGANG PASAR KARANGMANGU - Anisa Laeli Ramdani (INUMIYA: Jurnal Ekonomi Pembangunan, 2023)
The Kroya Market fire at the end of 2021 caused the relocation of market traders to the Kroya Bus Terminal location during the process of rebuilding the burned market. This of course had an effect on market traders' income, so the author was interested in conducting research with the title "The Influence of Business Location and Business Capital on Income Karangmangu Market Traders.” This research aims to determine the influence of business location and business capital on the income of Karangmangu market traders, which has an impact on the economy of market traders. This research uses descriptive quantitative data analysis methods with variables of business location, business capital and trader income. The sample from this research consisted of 77 traders. The results of data processing using multiple linear regression showed that partially the variables of business location and the influence of business capital had a significant effect on the income of Kroya Market traders. Likewise, simultaneously the two variables of business location and the influence of business capital have a significant effect on the income of Kroya Market traders. Based on the results of this research, it is hoped that the Cilacap Regency Government, in carrying out market relocation, will pay attention to location conditions and provide support for access to capital for market traders in order to improve their welfare.